Hubungan Konsep Diri Menantu dan Keterbukaan Diri Menantu dengan Tingkat Konflik Interpersonal pada Mertua yang Tinggal Bersama - Deffa Prameyta; Hedi Pudjo Santosa; Primada Qurrota Ayun (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
The relationship between in-laws and in-laws that exist consists of various kinds, namely conflict-filled relationships or harmonious relationships, especially if they both live under the same roof. This study aims to determine the correlation between the daughter/son-in-law's selfconcept and the daughter/son-in-law’s self-disclosure with the level of interpersonal conflict of mother/father in-laws who lived together. This research used Looking Glass Self Theory and Social Penetration Theory. This study used a sample of 100 people who in age from 19- 35 years old who are married and live with in-laws. This sample method used non-probability sampling with accidental techniques. The results showed the daughter/son-in-law's self-concept with the level of interpersonal conflict of mother/father in-laws who live together has a significance value of 0.000 ≤ 0.01, which means that there is a very significant correlation. This shows that Looking Glass Self theory can be applied in this study. The correlation coefficient is -0.558 means that it has a strong and negative level of correlation. This shows a negative correlation if the son-in-law's self-concept is low, the level of interpersonal conflict of mother/father in-laws who live together increases. While the daughter/son-in-law's self-disclosure with the level of interpersonal conflict of mother/father in-laws who lived together have a significant value of 0.000 ≤ 0.001, which means there is a very significant relationship. This shows that Social Penetration Theory can be applied in this study. The correlation coefficient is -0.553, which means it has a strong and negative level of correlation. This shows a negative correlation if the daughter/son-in-law's self-disclosure is low, the level of interpersonal conflict of mother/father in-laws who lived together increases. Likewise, vice versa. Therefore, the daughter/son-in-law should improve their self-concept and self-disclosure so that the level of interpersonal conflict of mother/father in-laws who lived with them decreases. It is recommended for further research to review other variables of the in-laws relationship.